Regulatory aspects of artificial intelligence on blockchain - Tehrani, Pardis Moslemzadeh (Advances in computational intelligence and robotics (ACIR) book series., 2022)
"This book provides relevant legal and security frameworks and the latest empirical research findings in the area of blockchain and AI striving to identify and overcome the legal consequences of the application of Artificial Intelligence into the blockchain system"--